The role of personality type in overcoming workplace distractions - Salman Zulfiqar; Muhammad Rafay Khawar; Binesh Sarwar; Chunhui Huo (Journal of Innovation & Knowledge (JIK), 2023)
Excessive usage of social networking sites (SNSs) has permeated individuals' daily lives, leading to negative outcomes such as reduced cognitive performance and physical problems. Regardless of the threat, few researchers have examined the negative consequences of social networking sites on employee performance. This study uses cognitive theory and Eysenck's theory of personality as the foundation of the proposed model to explore whether excessive social networking site usage deteriorates workers' cognitive performance. We propose that excessive use of social networking sites negatively impacts employees' cognitive performance, that extroverted individuals are the most distracted by social networking sites compared to introverts, and that ambiverts are the least distracted by them in the workplace. A sample of 266 Chinese and Pakistani users of social networking sites from the software house service sector was tested empirically to validate the proposed model. This study contributes to mitigating the negative impact of excessive SNS usage by implementing and using digital well-being applications to control addictive behavior. Furthermore, it provides theoretical and practical insights for organizations to improve employees' cognitive performance.
Keywords: L20; L29; 650; Cognitive performance; Excessive use of social networking sites; Personality type; Task distraction